Absorption of Bile Pigments by the Gall Bladder - Ostrow, J. Donald (1967)
A technique is described for preparation in the guinea pig of an in situ, isolated, vascularized gall bladder that exhibits normal absorptive functions. Absorption of labeled bile pigments from the gall bladder was determined by the subsequent excretion of radioactivity in hepatic bile. Over a wide range of concentrations, unconjugated bilirubin-(14)C was well absorbed, whereas transfer of conjugated bilirubin proceeded slowly. Mesobilirubinogen-(3)H was absorbed poorly from whole bile, but was absorbed as rapidly as unconjugated bilirubin from a solution of pure conjugated bile salt. Bilirubin absorption was not impaired by iodoacetamide, 1.5 mM, or dinitrophenol, 1.0 mM, even though water transport was affected. This indicated that absorption of bilirubin was not dependent upon water transport, nor upon energy-dependent processes. The linear relationship between absorption and concentration of pigment at low concentrations in bile salt solutions suggested that pigment was transferred by passive diffusion. At higher pigment concentrations or in whole bile, this simple relationship was modified by interactions of pigment with bile salts and other constituents of bile. These interactions did not necessarily involve binding of bilirubin in micelles. The slow absorption of the more polar conjugates and photo-oxidative derivatives of bilirubin suggested that bilirubin was absorbed principally by nonionic, and partially, by ionic diffusion. Concentrations of pure conjugated bile salts above 3.5 mM were found to be injurious to the gall bladder mucosa. This mucosal injury did not affect the kinetics of bilirubin absorption. During in vitro incubation of bile at 37°C, decay of bilirubin and hydrolysis of the conjugate proceeded as first-order reactions. The effects of these processes on the kinetics of bilirubin absorption, and their possible role in the formation of “white bile” and in the demonstrated appearance of unconjugated bilirubin in hepatic bile, are discussed.